Romantisme Kehidupan Sebagai Ide Penciptaan Karya Seni Lukis - Aliyahzahra, Anitia; Adnyana, I Wayan; Kondra, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2026)
Romantic art has long been a means of expression that allows people to explore various aspects of life outside the boundaries of conventional romance. In this report, the author approaches the topic of romance from a broader perspective, not only as an embodiment of love and human social interaction but also as an expression of natural simplicity and beauty as well as emotional depth. Inspiration from the Romantic art school motivates writers to create works of art that visualize the beauty and complexity of individual lives through self-portraits and portraits of people important to the writer. Method of making this work. Art includes the stages of contemplation, idea processing, improvisation, and conception, which are systematic steps in developing an idea from conception to realization. The idea for this work of art emerged from the author's personal experience in depicting the people closest to him, and pets were the main subject. The process of viewing this work is made using a collage technique combined with acrylic paint, thus creating a dynamic aesthetic, full of emotional meaning. This work of art not only represents the physical dimensions of the object depicted but also reveals its depth. relationships and hidden meanings behind them. With an emphasis on facial expressions and harmonious use of color, this work invites viewers to reflect on the beauty of human relationships and appreciation of shared values. Through this study, the author hopes to inspire an experience of contemplation and deep appreciation for the romance of life in all its splendor.